THE INFLUENCE OF SMARTPHONE USAGE, LEARNING PATTERNS, AND LEARNING CULTURE ON LEARNING MOTIVATION THROUGH SELF EFFICACY IN HIGH SCHOOL STUDENTS IN SAMARINDA CITY - Umi Fitria; Enny Kartini; Muaini Muaini; Surahman Surahman (Program Studi PGSD Universitas Flores, 2025)
In today's digital era, smartphones have become an integral part of everyday life, especially among students. In Samarinda City, smartphone usage among senior high school students is increasing, and this has a significant impact on their learning patterns and learning culture. In this context, it is important to understand how smartphone use, study patterns, and learning culture interact and influence students' learning motivation through self-efficacy. The purpose of this study was to determine the effect of smartphone use, study patterns, learning culture, and self-efficacy on learning motivation. This research was conducted at high schools in Samarinda City. The population in this study consisted of 1,640 grade 12 students. The sample was taken using a proportional random sampling technique, which amounted to 410 respondents. The data collection techniques used were questionnaires, interviews, and documentation. Data analysis uses CFA. Data were analyzed using descriptive and inferential statistical techniques. The model fit test uses SEM with the LISREL program. The results of this study are: (1) Learning patterns and learning culture have a positive and significant effect on learning motivation, while smartphone usage and self-efficacy have no effect on learning motivation., (2) Smartphone use, learning patterns, and learning culture affect self-efficacy., (3) The use of smartphones, learning patterns, and learning culture has no effect on learning motivation through self-efficacy. This study concluded that there is a significant influence of learning patterns and learning culture on learning motivation.